2022
DOI: 10.3390/nu14112288
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Prevents Key Mechanisms of Obesity-Related Complications in Visceral White Adipose Tissue of Obese Pregnant Mice

Abstract: With the gaining prevalence of obesity, related risks during pregnancy are rising. Inflammation and oxidative stress are considered key mechanisms arising in white adipose tissue (WAT) sparking obesity-associated complications and diseases. The established anti-diabetic drug metformin reduces both on a systemic level, but only little is known about such effects on WAT. Because inhibiting these mechanisms in WAT might prevent obesity-related adverse effects, we investigated metformin treatment during pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…For instance, the levels of lecithin cholesterol acyltransferase (LCAT), which is a crucial enzyme for HDL metabolism [ 23 , 24 ], are significantly increased, mirroring IR and diet-induced obesity [ 25 ]. The levels of MYH10 are increased in obese pregnant mice [ 26 ], and its interaction with insulin-dependent glucose transporter 4 (GLUT4) regulates adipocyte function and adipogenesis [ 27 ]. The findings of these studies are conceptually consistent with our results that the levels of MYH10 were significantly decreased in children with obesity who had undergone weight loss intervention and may play an important role in weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the levels of lecithin cholesterol acyltransferase (LCAT), which is a crucial enzyme for HDL metabolism [ 23 , 24 ], are significantly increased, mirroring IR and diet-induced obesity [ 25 ]. The levels of MYH10 are increased in obese pregnant mice [ 26 ], and its interaction with insulin-dependent glucose transporter 4 (GLUT4) regulates adipocyte function and adipogenesis [ 27 ]. The findings of these studies are conceptually consistent with our results that the levels of MYH10 were significantly decreased in children with obesity who had undergone weight loss intervention and may play an important role in weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin therapy during gestation reduces weight gain and visceral white adipose tissue mass. It offers plenty of effects suitable for inhibiting obesity’s key mechanisms in visceral white adipose tissue, such as inflammation, oxidative stress, and tissue dysfunction [ 67 ]. A previous animal study found that metformin has a dual effect on the differentiation of 3T3-L1 preadipocyte cells by promoting or suppressing adipogenesis and that lower concentrations of metformin induce 3T3-L1 preadipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%